OPTIMIZING DATABASE MANAGEMENT FOR INDIVIDUALS WITH DISABILITIES: A MANAGEMENT INFORMATION SYSTEM FRAMEWORK UTILIZING CODEIGNITER IN SUKOHARJO REGENCY - Tino Feri Efendi; Dewi Muliasari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research aims to optimize database management for individuals with disabilities in Sukoharjo Regency, by utilizing a Management Information System (SIM) that uses the CodeIgniter framework. The case study was conducted at the SEHATI Disabled Community, involving 50 community members with various types of disabilities. An evaluation of member needs and expectations revealed a desire for better accessibility, efficient recording of activities, and better management of health information. The implemented system includes member registration, activity management, medical records, and responsive interface design to achieve universal accessibility. Testing and performance evaluations show increased efficiency and user satisfaction. Conclusions and recommendations involve continued training, feature improvements based on feedback, and further implementation of security policies. Keywords: Database Optimization, Management Information Systems, CodeIgniter, Disability, Universal Accessibility, SEHATI Disabled Association, Sukoharjo Regency.